Film Front Weimar Representations of the First World War in German Films from the Weimar Period (1919-1933) - Kester, Bernadette (Film Culture in Transition, 2003)
This first book-length study shows how Germany tried to reconcile the horrendous experiences of the FirstWorld War through the films made in 1919-1933. Drawing on the analysis of twenty-five such films, and covering a wide range of documentaries as well as feature films on the reasons for the outbreak of the war, life at the front,war at sea and the home front, the author sketches out the historical and cultural context, including reviews and censors' reports, in which these films were made and viewed. This title is available in the OAPEN Library - http://www.oapen.org.